음이온 교환수지를 이용한 인제거 향상 - 남주희; 이상협; 최재우; 홍석원; 안병렬 (대한상하수도학회, 2013)
The concern for dissolved phosphate in water/wastewater has been increasing because of the risk for eutrophication. A variety of conventional and advanced technologies were applied to meet the enforced new regulation of phosphate around the world. However, there still remained a lot of challenge because most introduced/developed method, for example, biological and physic-chemical treatment is not easy to satisfy the new regulation of phosphate in water. In order to meet the new regulation, the application of ion exchanger has been tried which showed that the removal efficiency for phosphate was strongly determined by in the presence of the competing ion, especially sulfate. As results, a new class of ion exchanger governed by ligand exchange was developed and investigated to increase the selectivity for phosphate. The current study using organic/inorganic anion exchanger developed with Lewis acid-base interaction confirms the selectivity for phosphate over sulfate. According to isotherm test and column test, the value of the maximum phosphate uptake (Q) showed 64 mg/g as po4 and the breakthrough for phosphate occurs after 1000 min and completely finishes at 2500 min, respectively.